A comprehensive computational study of Millets derived phytochemicals as potential inhibitors of NACHT domain of NLRP3 inflammasome: Molecular docking, molecular dynamics simulation, MM-PBSA free energy calculation and DFT analysis (Indian Journal of Biochemistry and Biophysics (IJBB), 2024)
The NLRP3 inflammasome is a vital constituent in the innate immune response, which regulates the caspase-1 activation for the production of proinflammatory cytokines IL-1 and IL-18. NLRP3 inflammasome activation is the main cause of many inflammatory diseases and can contribute to onset of metabolic disorders. There is an urgent need to develop drugs that can inhibit activation of inflammasome. Now a days, millets are known to be rich in polyphenols, which have potential to become drug molecules. In the current study, we investigated the efficacy of phytochemicals of millets against NACHT domain of NLRP3inflammasomeby using various In silico techniques. The interaction affinities of polyphenolic compounds towards NLRP3 was evaluated via intramolecular by Quantum Mechanic, intermolecular by Molecular Docking, and spatial by Molecular dynamics simulations. Isovitexin, Kaempferol, Quercetin, Syringic acid Tricin showed highest (most negative) CDOCKER interaction energy among all phytochemicals and positive control MCC950. Two best compounds Isovitexin and Kaempferol along with MCC 950 were further studied through dynamic simulation, which showed their stability at active site. MM-PBSA binding free energy of phytochemicals Isovitexin, Kaempferol and MCC950 are -51.5813 kcal/mol, -26.6370 Kcal/mol and -12.7006 kcal/mol, respectively, which indicate high degree of binding compared to positive control further these compounds were studied through DFT to determine chemical stability.